Ocular trauma - Bhupally, Anil Kumar; Chigiri, Sindu Sulekha; M., Swathi; M., Rohini; T., Shruthi (International Journal of Research in Medical Sciences, 2017)
Background:Ocular trauma has been a neglected problem. Worldwide there are approximately 1.6 million people blind from eye injuries and 2.3 million bilaterally visually impaired and 19 million with unilateral visual loss; this being a most common cause of unilateral blindness today.The objective of the study was to analyze ocular injuries with respect to the mode of injury, sites involved, and visual outcome. Methods: This is a hospital based retrospective observational study. Cases included in the study presented to the casualty and Ophthalmology Department in Chalmeda Anand Rao Institute of Medical Sciences from May 2013 to January 2015. Trivial injuries resulting in superficial foreign bodies and uncomplicated superficial corneal abrasions were excluded. Results:In this study, 76 cases presented with ocular injuries. Majority of the patients were males (83.87%) and the most common age of presentation was between 17 to 39 years (34.8%). Most common mode of ocular trauma in our study was closed globe injury due to blunt trauma (77.6%) followed by chemical injuries (13%) and least common was penetrating trauma. Anterior segment involvement included acute corneal edema (11 cases), scleraltear (10 cases), corneal tears and iris prolapse (9 cases), traumatic cataract (9 cases), traumatic subluxation of lens (8 cases), traumatic subluxation of IOL (5 cases), phacocele (1case), lid laceration (4cases). Posterior segment injuries include traumatic optic neuropathy (6cases) and Berlin’s edema (4cases), sub retinal hemorrhage (4cases), vitreous hemorrhage (4cases) and macular hemorrhage (1case).Occupation based injuries were 26 cases (43.3%). A poor visual outcome was associated with posterior segment involvement. Visual acuity in 41 patients was better or equal to 6/12 (54.3%), 15 patients (19.7%) were only able to perceive light and 2 patients (2.6%) underwent enucleation. Conclusions:This study reinforces that occupational trauma and domestic trauma were common causes and that trauma can cause any extent of damage to ocular structures, and the final visual outcome is dependent on the structures injured and treatment given within appropriate time.